Provider-oriented moral hazards associated with the prescriptions paid by insuring Organizations - Ebrahim Jaafaripooyan; Batoul Ahmadi; Baheshte Ebrahimi (بیمارستان, 2021)
Background and Aim: Expenditure in the health sector requires appropriate resources management. This study was conducted to determine the amount of moral hazards associated with the service providers in the medication prescriptions paid by an insurance organization. Methods: Study population included paid pharmaceutical documents in Tehran province in 2019. 2000 prescriptions for 500 insured people were randomly selected from the database of the organization. Two indicators (the number of suspicious prescriptions based on the incompatibility of a drug with the history of the disease or the drug spectrum of an insured and the number of prescriptions with a financial burden higher than the average usual burden of a normal patient) were matched with transcript data and analyzed with SPSS version 24. An experienced pharmacist was consulted to examine the drug spectrum of all prescriptions. Results: 5.4% of total prescriptions were incompatible drugs and 6.4% had created extra financial burden. The highest incidence of risks by speciality was related to general practitioners (16 % with a surplus financial burden of 87/500/000 Rials). The highest number and amount of risks in Rials per insured group was related to supervisors (63 % with a surplus financial burden of 26/000/000 Rials). The risk in the military centres’ prescriptions were more than private and governmental centres and it was relatively equal in contracted (48%) and non-contracted (52%) centres. Conclusion: The abuse in the health service provision is a high risk for  health care managers  in countries that have health insurance programs which their intelligent tracking reduces many of the insurers’ costs and prevent the shortage of vital medicines.